EVALUASI MODEL CIPP (CONTEXT, INPUT, PROCESS, PRODUCT) PADA PELAKSANAAN PEMBELAJARAN LURING DIMASA PANDEMI COVID-19 SD INPRES 109 PERUMNAS KOTA SORONG - Astati Astati; Agus Yudiawan; Erwinestri Hanidar Nur Afifi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2021)
This study aims to determine the evaluation of offline learning during the COVID-19 pandemic using the CIPP program at SD Inpres 109 Perumnas, Sorong City. This study uses a quantitative descriptive approach with a population of all high-grade students (IV-VI) totaling 334 students. Sampling using non-probability sampling with purposive sampling technique sampling. The number of samples was set at 182 students using the Slovin formula with a significance level of 5%. Data were collected by distributing questionnaires. The data analysis used was descriptive quantitative. The results of the study show that the application of the offline learning model has been carried out well in the midst of the covid-19 pandemic. The context, input, process, and product components on average are in the very high category. In addition, a policy of time for teaching and learning activities must be carried out so that the learning time is more extended.